2019
DOI: 10.17770/etr2019vol2.4166
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Web-Based Idea Management System Based on Practical Evidence

Abstract: During the last decade software developers have put increasing focus on developing information systems supporting decision making, collaboration, knowledge and idea management. Idea management systems (IMS) - manageable systematic tools to generate and evaluate ideas - are an important element within this trend.   Web-based IMS are used by many well-known organizations, e.g. Volkswagen, Cisco, Microsoft, Lidl, GE Healthcare, Nestle, Procter and Gamble, Tchibo, Henkel, Roche, Fujitsu, Boeing, Goodyear, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This study is built on the basis of previous studies of a commercially available web-based IMS and analysis of case studies of the IMS application where the main benefits of IMS are identified (Mikelsone, Volkova & Liela, 2019a;2019b). In this research, authors collected the data with the survey to research materialization of these benefits in an organization.…”
Section: Introductionmentioning
confidence: 99%
“…This study is built on the basis of previous studies of a commercially available web-based IMS and analysis of case studies of the IMS application where the main benefits of IMS are identified (Mikelsone, Volkova & Liela, 2019a;2019b). In this research, authors collected the data with the survey to research materialization of these benefits in an organization.…”
Section: Introductionmentioning
confidence: 99%